A Analisis Soal Etnomatematika SASAMBO dalam Pembelajaran Matematika Dasar - Heriyanto Heriyanto; Yulia Nurrahmawati (Mandalika Mathematics and Educations Journal, 2025)
This study aims to analyze the integration of local SASAMBO (Sasak, Sumbawa, and Mbojo) cultural elements into ethnomathematics-based Basic Mathematics learning problems. The approach used was descriptive qualitative, with data sources consisting of evaluation questions that integrate mathematical concepts within a cultural context. Data were analyzed through stages of reduction, presentation, and conclusion to uncover the relevance between local cultural values ​​and mathematical concepts such as sets, logic, and meaning. The results show that using the SASAMBO cultural context in mathematics problems can improve conceptual understanding, strengthen character, and foster student learning motivation. This improvement can be seen in the evaluation results which show progress in mastery of the material and the ability to connect mathematical concepts with real situations that are culturally relevant. Ethnomathematics-based problems make learning more contextual, meaningful, and interactive because they connect cultural experiences with formal mathematical concepts. The application of SASAMBO ethnomathematics can be an effective strategy in developing Basic Mathematics learning that is relevant to local culture and supports the implementation of Independent Learning.